The motive of love melancholy and the variability of feminine images in the structure of the "melancholy of life" ("l'ennui de vivre") complex - Онопрієнко, Анастасія Дмитрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article deals with the connection of the motive of love melancholy with the motive complex of the "melancholy of life" ("l'ennui de vivre"), examines the specifics of its realization in the female images in the poetry of French and Russian symbolism.In addition to internal conflict, the decadent worldview is characterized by the opposition of "I – Other", including the conflict of male and female primes, which is the main factor in the origin of the motive of love melancholy. Female images of the Decadence era are ambivalent. On the one hand, the woman for the decadent lyric hero is a beast creature, the embodiment of an animal principle. The passion for woman is destructive, and the image of a woman is represented by the "femme fatale". On the other hand, at the same time, the romantic concept of "beautiful lady", a female angel, whose image is devoid of erotic context and embodies an unattainable ideal, striving for which emphasizes the horror of being and the subjective feeling of "l'ennui de vivre", is developing. In Russian poetry of symbolism, the connection of love motives with the "melancholy of life" is revealed mainly through the motives of separation, lost love. The motive of lost love is related to the intimate lyrics of I. Annensky and P. Verlaine. Instead, in B. Bryusov's poetry, the love appears as an irreconcilable gender conflict, a duel between a man and a woman, doomed to a fatal passion. Thus, the motive of love melancholy is a part of the structure of the motive complex "l'ennui de vivre" because of the specificity of the implementation of female images and their attitude to the lyrical hero.